INCIDENCIA DE MALEZAS EN EL PERIODO CRÍTICO DE ARROZ (Oryza sativa) Y SU EFECTO SOBRE EL COMPORTAMENTO AGRONÓMICO EN LA ZONA DE BABAHOYO - Monserrate Barco, David Ricardo (2020)
The present experimental work was carried out in the lands owned by Mr. Ángel Calero Jiménez, located in the "Cedege" irrigation project, in the Rcto. Palmar, Zone 6, belonging to the canton Babahoyo, Province of the Rivers. Seed was used as seed material of rice SFL-11 and INIAP Cristalino 1480. The treatments studied were rice varieties with presence of weeds at 15, 30, 45 and 60 days after transplanting and an uncontrolled control. The experimental design "Complete Random Blocks" was used, in Factorial arrangement A x B, with ten treatments and three repetitions. Factor A was made up of rice varieties and Factor B due to the presence of weeds. All the variables evaluated were subjected to the analysis of variance and to determine the statistical difference between the means of the treatments, the Tukey statistical significance test was used at the 0.05 level. During the development of the crop, the following tasks and agricultural practices were carried out, such as Land Preparation, Sowing, Irrigation, Fertilization, Weed Control, Phytosanitary Control and Harvesting. Based on the results obtained, it was determined that the effect of the weeds was reported in the critical period of rice (Oryza sativa) in the Babahoyo area; the SFL-11 rice variety positively influenced weed attack; the agronomic characteristics of plant height, tillers and panicles / m2, days to flowering, panicle length, grains per panicles and weight of 1000 grains obtained positive results in the SFL-11 variety with presence of weeds 30 days after the transplant ; in the length of roots, fresh and dry biomass of the aerial part, the rice varieties studied were not statistically significant, however variation in the interactions was reached, with the presence of weeds standing out at 30 days after the transplant; the fresh and dry biomass of the root obtained higher average in the SFL-11 variety with presence of weeds at 30 days after the transplant and the highest yield of the crop and net benefit was presented in the SFL-11 variety with presence of weeds at 30 days after the transplant with 5161 kg / ha and economic gain of $ 483.04.